Trace Adsorptive Removal of PFAS from Water by Optimizing the UiO-66 MOF Interface - Ilić, Nebojša (Advanced materials (Deerfield Beach, Fla.), 2025)
© 2024 The Author(s). Advanced Materials published by Wiley‐VCH GmbH.